Mechanical Behavior of Soil Foundations Reinforced with Geosynthetics Exposed to Normal and Reverse Fault Ruptures - Ahmadi, Nabiollah; Fadaee, Meysam (Periodica Polytechnica Civil Engineering, 2023)
Surface fault ruptures damage structures which are located at the intersecting zones of active faults. It is essential to consider the undesirable effects of surface fault ruptures when designing structures. Geotechnical measures such as reinforced soil foundations effectively mitigate the hazards related to surface faults. The present work conducted a series of tests on foundations reinforced with geosynthetics, including geogrids, geocells and geogrid-geocell layers. These tests simulated the behavior of5 m-wide strip footings located in 6-m thick alluvium that had been displaced 60 cm. A total of 12 disparate tests in terms of the number and type of reinforcement were conducted at a scale factor of 10. Image analysis of the results indicated desirable behavior for reinforced soil foundations in terms of reduced angular distortion, uniform settlement and deviation of the fault path. For normal fault rupture, the angular distortion of foundations reinforced by one geogrid layer, one geocell layer, one geogrid-geocell layer or two or three geogrid layers decreased by 60%, 30%, 70%, 80% and 80%, respectively. These results also revealed that an increase in the number of geogrid layers to more than two layers caused an insignificant decrease in angular distortion. The decrease in angular distortions observed for soil foundations reinforced by one geogrid layer, one geocell layer and one geogrid-geocell layer were 7%, 16% and 40%, respectively, for reverse faulting. The performance of a reinforced soil foundation subjected to normal faulting was more acceptable than that for reverse faulting.